Quick Response Code Indonesia Standard in increasing the effectiveness of collecting Zakat, Infaq and Shadaqah Funds - Afifudin Afifudin; Sulton Sholehuddin; Agus Hermawan; Puji Handayati (Trigin Publisher, 2023)
This research aims to explain how effective the quick response code Indonesia standard (QRIS) is in the growth of increasing the collection of zakat, infaq and shadaqah funds in Baznas Kaya Malang. To answer the question above, the research design used is descriptive qualitative research involving three groups of informants (administrators, managers and muzakki or the public). Based on the results of the study, it shows that the level of effectiveness of collecting ZIS funds through digital QRIS is generally not effective. This is evidenced by the level of effectiveness in 2020 and in 2021 the level of effectiveness reached 24%, thus getting the predicate not yet effective. This shows that the implementation of digital QRIS in Baznas Malang City cannot be said to be effective in its collection due to the lack of understanding and trust of muzakki in digital QRIS.